MANIFESTASI KINERJA LINGKUNGAN DALAM PERSPEKTIF ILMU AKUNTANSI DI PERUSAHAAN KOTA CILEGON - anti, Pebri; Ismail, Tubagus; Muchlish, Munawar; Komarudin, Mochamad Fahru (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
Environmental problems with pollution are generally caused by waste resulting from poorly managed waste disposal systems from the production process. Around 64 of the 470 watersheds are in critical condition. The causes are varied, including industrial waste containing various chemicals. This is because the use of corporate environmental accounting is less proactive to the management of the application of corporate environmental management accounting that is not good. The results of the proper assessment of the company's environmental performance in Banten 2017-2018 there were 9 companies that received a red rating greater than the 2016-2017 assessment year which only 5 companies. This type of research is a comparative causal study. Based on the type of data, this research is a quantitative study, because the data used is in the form of numbers. The method used in data collection in this study is to use survey techniques, namely data collection by questionnaire in 36 companies in the city of Cilegon who follow environmental proper. In this study the data was processed using PLS static tools to have different characteristics from previous studies. Based on the results of the study it can be concluded that Environmental Management Accounting, Environmental Strategy, Physical environmental accounting, Monetary environmental accounting have a positive and significant effect directly on Environmental Performance. And the Environmental Strategy has a positive and significant effect on Environmental Management Accounting directly.